Fungsi Badan Usaha Milik Desa dalam Meningkatkan Kesejahteraan Masyarakat : Studi BUMDes Serang Makmur Sejahtera, Desa Serang, Kabupaten Purbalingga - Huda, Rojaul; Laksmono, Bambang Shergi (Jurnal Ilmu Kesejahteraan Sosial, 2020)
One of the efforts to reduce poverty and improve community welfare is through entrepreneurship. Village owned enterprises (BUMDes) are one of the places for entrepreneurial learning for rural communities. Likewise, what happened at BUMDes Serang Makmur Sejahtera in Serang Village, Karangreja District, Purbalingga Regency. The research objective is to gather information about the function of BUMDes in improving the welfare of the community in rural areas. This article uses a qualitative research method with a descriptive type. Data were collected by observation and in-depth interviews with BUMDes managers, village officials, and village communities. Based on this research, it is found that the existence of village-owned enterprises (BUMDes) Serang Makmur Sejahtera has a function of public welfare, namely in the community economy, employment, education, health and recreation directly to improving public public services such as health services and improving village infrastructure. Recommendations from this study are to improve BUMDes business units that are environmentally based, provide social security to BUMDes managers and employees, and improve the capabilities and skills of BUMDes managers and employees.